Role of queuosine tRNA modification in the parasitic protist Trypanosoma brucei - Kulkarni, Sneha Sunil (Jihočeská univerzita, 2021)
This study analyzes the queuosine (Q) tRNA modification and the enzyme responsible for Q formation, the tRNA guanine transglycosylase (TGT), in the parasitic protist Trypanosoma brucei. We describe the interdependence of Q modification and tRNA subcellular trafficking, and how these two factors regulate codon biased translation. The effect of Q on translation has serious implications in the virulence of the parasite inside the mammalian host.
Role of queuosine tRNA modification in the parasitic protist Trypanosoma brucei
Keywords: Queuosine; tRNA guanine transglycosylase; tRNA modifications; tRNA traficking; mitochondria; synonymous codon usage; Queuosine; tRNA guanine transglycosylase; tRNA modifications; tRNA traficking; mitochondria; synonymous codon usage